A Review of the Sameness-Differences Between Identity and Concepts Related to Identity - Altunoğlu, Mustafa (Journal of Applied And Theoretical Social Sciences, 2023)
In this study, the relationship between identity and identity-related concepts (self, personality, social self, personal identity, social identity, collective identity, narrative identity) in social and political theory will be examined. Some of the concepts listed, especially the concepts of identity and self, are often used interchangeably. In recent years, these concepts have occupied a predominant place among the subjects discussed in disciplines such as philosophy, anthropology, sociology, political science and psychology. Different meanings can be attributed to each of these concepts depending on the tendencies of the disciplines. These two basic situations can often lead to conceptual confusion or prevent or delay the proper understanding of many social issues or problems that require the use of relevant concepts. This study aims to make a modest contribution to solving these problems.